Metronomic chemotherapy in platinum-insensitive failures and/or early failures postmultimodality management in oral cancers - Vijay M Patil; Vanita Noronha; Amit Joshi; Rakesh Pinninti; Sachin Dhumal; Atanu Bhattacharjee; Kumar Prabhash (Indian Journal of Medical and Paediatric Oncology)
Purpose: Oral cancer patients with platinum-resistant disease and or early failures have limited treatment options. This analysis was planned to study the efficacy of metronomic chemotherapy in this group of patients. Materials and Methods: This was a retrospective analysis of oral cancer patients who had squamous cell carcinoma and had an early failure and/or platinum-insensitive failure. Early failure was defined as a failure either within 1-month of adjuvant radiotherapy or within 6 months of chemoradiation (CTRT). A sample size of 100 patients was selected for this study. If ≥39 of 100 patients would have survived at 6 months with metronomic chemotherapy, then additional studies would be warranted. Results: The ECOG PS was 0-1 in 92 patients and 2 in 8 patients. The subsite of primary was buccal mucosa in 38 patients (38%), anterior two-third tongue (oral tongue) in 51 patients (51%), and alveolus in 11 patients (11%). The median estimated overall survival was 110 days (95% confidence interval [CI]: 85-134 days). The proportion of patients surviving at 6 months was 26.4% (95% CI: 17.9-35.6). Conclusion: Metronomic combination of methotrexate and celecoxib failed to meet its prespecified efficacy limit and should not be used in these patients as routine.